A disciplina e a indisciplina na sala de aula em uma escola pública estadual de São Paulo - Sena, Mary Anne de Oliveira (2020)
This study is affiliated to Educational Management and Practice Program, Universidade Nove de Julho (PROGEPE – UNINOVE), specically to research and intervention line – Learning Methodology and Teaching Practices (LIMAPE). It was proposed as object of research the good and bad behavior in the classroom. Starting from this point some questions risen and they motivated and guided this specific subject development: what may be considered as good and bad behavior into school environment? Is it possible to build dialogue between teachers and students about good and bad behavior into the classroom? Starting from these questions, it was delimited as a general objective to mediate the dialogue and the student’s listening regarded to the basis from teachers and students’ relationship into the classroom. As the objectives of this research we raised: (1) identify the relationship among disciplinary processes established in the classroom and under students’ vision; (2) to check the interactions and dialogue possibilities among students and teachers; (3) to analyze the relationship between good and bad behavior into the classroom as a reflexing possibility; and (4) propose from the data collected and analyzed, together with the study participants, possible conflicts mediation risen by bad behavior. From the objectives introduced, this research was developed following a qualitative approach, applied from a research-action-intervention, based in the principle of hearing all participants in the process. This research was developed from the observation and intervention of its own teacher’s práxis, in other words, the relationship teacher-researcher and its students, when they could talk and think about their difficult in listening, talking and modifying the interdisciplinary environment in a way that it is possible to think about it. The instruments used in data collection were: recorded and late transcribed talking, questionnaires with open questions and observation records. It was defined as the research universe a public state school from east zone of Sao Paulo, school which will be called under the codename Transformation. As researches subjects were taken thirty-two students from the 5th grade and early years and the researcher teacher. To fulfills proposals, this research is based on Aquino, Estela, Vasconcellos and Freire’s studies. The research main results have shown that the dialogue had allowed the perception process about the correct behavior to the learning development, mainly from those students who had shown behavior difficulties and which students who were considered as having bad behavior. It was possible to realize advances regarded to the living conditions among the subjects in the classroom, mainly the ones previously considered as having bad behavior.